The Influence Of Price, Product Quality And Brand Image On Purchasing Decisions Purchase Of Bimoli Cooking Oil In The City Of Bengkulu - Arzil Azizah Saputra; Oni Yulianti; Wagini Wagini (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effects of price, product quality and brand image on purchasing decisions for Bimoli Cooking Oil in Bengkulu City. Based on the research results, the sample obtained in this research was 110 using the random sampling method. Based on the results of the multiple linear regression research, it showed that Y=63,893 + 0, 289 + -0, 345 + 0, 107 + 8, 158 which proves that price, product quality and brand image have a positive influence on purchasing decisions for Bimoli Cooking Oil in Bengkulu City. The results of the T test show that the price has T count> T table (1.659 > 2.556) and a significance value of 0.012 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, which means that price has a positive and significant effect on purchasing decisions for Bimoli Cooking Oil in Bengkulu city. Product Quality Test Results (X2) show tcount 3.739 > ttable 1.659 and significant 0.000 < 0.05. Therefore, the results of the Ha hypothesis are accepted and Ho is rejected, meaning that product quality has a positive effect on the purchasing decisions for Bimoli Cooking Oil in Bengkulu City, and the results of the Brand Image Test (X3) show tcount1.081>ttable 1.659 and significant 0.282>0.05, therefore the results of the Ha hypothes is rejected and Ho accepted, meaning that Brand Image has no significant influence the purchasing decisions for Bimoli Cooking Oil in Bengkulu City. Thus, the F test shows that the results of comparing the Fcount value with Ftable means that the Fcount value is greater than Ftable, namely 5.875 > 2.69, so it can be concluded that the hypothesis is accepted, meaning there is a simultaneous influence between Price (X1), Product Quality (X2) and Brand Image (X3) on purchasing decision variable (Y), this can be seen at the significance level of 0.001 < 0.05.